Medical rehabilitation in the combination treatment of rheumatic diseases: a review - A. E. Karateev; M. V. Sukhareva; A. M. Lila (Научно-практическая ревматология)
Medical rehabilitation is a set of non-drug methods aimed at reducing pain and functional disorders, restoring working ability, social activity, and mental stability in patients. This is a necessary part of treatment in patients with rheumatic diseases, which is as important as pharmacotherapy in many cases (for example, osteoarthritis, chronic nonspecific back pain, and spondyloarthritis). Unfortunately, many Russian physicians underestimate the possibilities of nondrug approaches, referring to the fact that the effectiveness of medical rehabilitation and physiotherapy methods have not been evaluated during clinical trials and their therapeutic significance has passed no serious test in the context of evidence-based medicine. This is not entirely true. This review presents data from a large number of clinical trials and related meta-analyses of studies evaluating the efficiency of the most commonly used medical rehabilitation techniques: cryotherapy, laser therapy, magnetotherapy, ultrasound therapy, percutaneous electroneuromyostimulation, acupuncture, manual therapy, massage, and therapeutic exercises.